EFEKTIFITAS MEDIA VIDEO PANORAMA DENGAN STRATEGI METAKOGNITIF DALAM PEMBELAJARAN MENULIS TEKS DESKPRIPSI SISWA KELAS VII SMPN 1 KARANGPLOSO - Sri Lestari (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
The purpose of this study is to describe the effectiveness of video to teach descriptive text in terms of content of idea of the text, organization, and accuracy of language use. This study uses a quantitative approach using an experimental class and no class control. Data were analyzed using t-test. The results showed that the application of video media panorama in learning to write text descriptions have demonstrated the effectiveness and improve the learning outcomes of students of class VII SMPN 1 Karangploso in the academic year 2015/2016.